Catalytic Conversion of Short-Chain Alcohols on Pd Single-Atom and PdAu Single-Atom Alloy Catalysts - Ouyang, Mengyao. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Charles Sykes.; Committee: Prashant Deshlahra, Matthew Panzer, and Shu Hu.; Keyword: Chemical engineering.